Pelaksanaan Sertifikasi Halal Lppom Mui Terhadap Produk Usaha Mikro, Kecil Dan Menengah (Umkm) (Studi Lppom Mui Provinsi Bengkulu) - Ahmad Farhan (Institut Agama Islam Negeri Bengkulu, 2019)
The issuance of Law Number 7 of 1996 concerning Products, Law Number 8 of 1999 Concerning Consumer Protection, Government Regulation Number 69 of 1999 reinforces the signal that the responsibility for halal food, beverage, medicines, cosmetics and other products is not only the responsibility of individuals and religious leaders alone, but also the responsibility of the government. Among the institutions responsible is the Food, Drug and Cosmetic Assessment Institute commonly called LPPOM. LPPOM MUI was established on January 6, 1989 to conduct halal examinations and certifications. According to Lukmanul Hakim as Director of LPPOM MUI Center that as a country that has the largest Muslim population, Indonesia has a big share in the world halal trade, reaching USD 197 billion of the total transaction estimated at US 1,600 Billion. Seeing the huge potential of global Muslim consumption in Indonesia, LPPOM MUI as a halal certification institution in Indonesia must be able to present halal guaranteed products. Because Indonesia is also a big market for imported products such as food, medicine, cosmetics and other used goods.